Religious Radicalism Behavior Through Suicide Bombings (Case Study: Surabaya Bombing) - Wishnu, Mochamad Bayu; Fauzi, Agus Machfud (Academic Solution Publisher, 2024)
In various religions, suicide is a wrong action. The phenomenon of suicide is one of the highest causes of death worldwide. Not only that, the cause of suicide is not only depression, but can also be caused by errors in religious interpretation. Radicalism and deviant ideology behavior, make individuals take actions that violate regulations in the government. The actions taken are not only uncomfortable around, but also endanger many people and cause casualties. One of the most inhumane behaviors is, Suicide Bombing. In this study, the researcher used a qualitative research method with a literature study approach. Literature study is an approach that uses various sources found in books, journals, theses, articles, which are relevant to the research being studied by the researcher. For the theory itself, the researcher studied through Emile Durkheim's Suicide theory because it was considered relevant to the existing research topic.